(untitled) (Research, Society and Development, 2023)
The National Curriculum Guidelines for the Graduation Course propose for Higher Education Institutions the use of Active Methodologies as facilitators in the teaching and learning processes, in which they provide the student with an active participation in the construction of knowledge. Thus, the objective of this integrative review, in light of the authors Souza et al. (2010), is to identify in the publications of dissertations and theses of Master’s, Professional Master’s and Doctorate programs how Active Methodologies have been used in Nursing courses by professors, as well as discussions about the use and knowledge about such methods , bearing in mind that it is through the training of future teachers that health education can meet the current needs of students and society. In view of the objective of this research, the observed results indicate that the Active Methodologies employed, identified in the context of this research, have a fundamental role in the training of future nurses, providing learning of course contents that enable the development of skills and competences capable of to respond to the needs presented by society.